Pengaruh Harga dan Pemasaran Digital terhadap Minat Pembelian Sayur Segar dan Kepercayaan Konsumen sebagai Variabel Intervening: Studi Kasus di Dusun Lengkong Desa Sayung (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
This study aims to analyse the effect of price and digital marketing on the interest in purchasing fresh vegetables and consumer trust as an intervening variable (case study in Lengkong Hamlet, Sayung Village). This study uses a quantitative method. The population used was 589 family cards in Lengkong Hamlet, Sayung Village. The sample size in this study was 100 respondents. Sampling was conducted using purposive sampling. Data analysis in this study used descriptive analysis and path analysis through the PLS (Partial Least Square) program using SmartPLS 4 software. The results of this study indicate that price has a positive effect on consumer trust, digital marketing has a positive effect on consumer trust, price has a positive effect on purchase interest, digital marketing has a positive effect on purchase interest, and consumer trust has a positive effect on purchase interest.